2018
DOI: 10.3390/su10093054
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution and Influencing Factors of Energy Consumption and Related Carbon Emissions from the Perspective of Industrialization and Urbanization in Shanghai, China

Abstract: Improvements of manufacturability and living standard driven by industrialization and urbanization typically cause a spike in total energy consumption (TEC) and related carbon emissions (TCEM). However, there have been few comparative studies to include industrial and residential energy consumption (IEC and REC, respectively) and related carbon emissions (ICEM and RCEM, respectively). Since China is a major emerging industrial country wherein urbanization is still ongoing, the present study was conducted in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Te positive impact of the average number of persons per household on REC is also found in other studies [53,[79][80][81][82]. Population growth will increase the demand for energy in the residential sector, and more residents consume more energy in daily life.…”
Section: Analysis Of the Impact Factorssupporting
confidence: 71%
“…Te positive impact of the average number of persons per household on REC is also found in other studies [53,[79][80][81][82]. Population growth will increase the demand for energy in the residential sector, and more residents consume more energy in daily life.…”
Section: Analysis Of the Impact Factorssupporting
confidence: 71%
“…Some have focused on the evaluation of CO 2 emissions in manufacturing [7], transportation [8,9], households [10,11], and buildings [12,13], and have found that these sectors are the main sources of CO 2 emission in urban areas. On the other hand, some scholars have suggested that the driving forces of urban CO 2 emission include population [14], the economy [15][16][17], technology [18][19][20], energy structure [21], urbanization [22], and spatial patterns [23,24], and have achieved many valuable conclusions. For example, the growing urban population and changing age structure exert positive effects on city-level emissions, while the downsizing of families and expansion of the migrant urban population fuel emissions [25]; growth in economic activity is the most fundamental contributor to the rising city-level emissions [26,27]; advancing technologies, in particular, breakthroughs in energy are the major means of lowering emissions [28] and rising emissions could be curbed by the adjustment of industrial structure and energy consumption patterns [29][30][31].…”
Section: Introductionmentioning
confidence: 99%